Grandparents of Autistic Children - The Best Support System - Mano, Elona (European Journal of Multidisciplinary Studies, 2016)
There is an increase of cases with autism spectrum disorder each year. The truth is that tens of thousands parents face a tremendous phase when they understand what autism is. Autism and autistic children are the focus of many studies in the last decades, but the focus is mainly on the children or the parents of these children. What happens with grandparents of autistic children? They suffer twice. They suffer for the grandchild and for their own son or daughter. In addition, maybe they blame themselves for that inherited “bad” gene that caused the disorder. To go further they maybe feel useless because of their age, their conditions or even their missing information. One of the biggest challenges in providing services to people with an autism spectrum disorder is that they need help 24 hours per day. Not only the grandparents, but even all the other members of the family can help a lot. This study is focused on grandparents`s point of view. What is autism and what does it mean for them to have an autistic grandchild? During the interviews the participants raised some important issues. To have grandchildren with autism is not easy, but at least grandparents are willing to help anyway. The important is that an autistic child feels the presence of everyone.